Asmachilca: Vernacular name of Eupatorium triplinerve Vahl, Aristeguietia discolor R.M. King & H. Rob., Aristeguietia gayana Wedd, Baccharis sp. (Asteraceae), Peru - Ganoza, Frizzi Judith (Ethnobotany Research and Applications, 2020)
Background: ¨Asmachilca¨ is the common name used by several species to solve respiratory problems such as asthma. The objective of this review is to obtain information on which species have the vernacular name ¨Asmachilca¨ in addition to comparing if the traditional uses coincide in Peru. Materials and methods: A search was carried out with databases such as Scopus and Google Scholar of: ¨asmachilca¨, ¨Asma Chilca¨, Eupatorium triplinerve, Aristeguietia discolor, Baccharis sp. 66 documents were collected from the review. Results: Three species share the name ¨Asmachilca¨ which are: Eupatorium triplinerve / Ayapana triplinervis / Eupatorium ayapana, Aristeguietia gayana / Eupatorium gayana and Baccharis sp. While Aristeguietia discolor / Eupatorium discolor has another vernacular name ¨Huamanchilca¨, ¨Chilca¨ or ¨Chilca negra¨, The four species (Asteraceae) have the same beneficial effect to treat respiratory problems such as bronchial asthma, due to their bronchodilator effect, in addition treat: coughs, colds, even as an anti-inflammatory. Conclusions: It is required to standardize ¨Asmachilca¨ for a specific type of species. All species have the same benefit for treating respiratory problems (bronchial asthma). The presence of compounds such as flavonoids and phenols could be mainly responsible for the relaxing effect of the endothelium and therefore has a bronchodilator effect. ¨Asmachilca¨ has dehydropyrrolizidine alkaloids (DHPA) and due to medicinal use this alkaloid can accumulate due to chronic use, causing liver problems. Key words: Eupatorium triplinerve Vahl, Aristeguietia gayana Wedd, Baccharis sp. asthma, anti-inflammatory.